STUDY OF THE COMPOSITION OF PISCO OF DIFFERENT VARIETY OF GRAPES FROM PISCO FROM THE MUST TO THE PRODUCT (PART II - THE PISCO) - Garrido S., Alberto (2008)
Pisco is produced from fermented grape seven Pisquera grapes. In this second part is reported the composition of pisco. The analysis was performed using the method USAQ-ME-11 by gas chromatography with mass spectroscopy.